DECISION SUPPORT SYSTEM TO DETERMINE THE BEST ONLINE SHOP COLLEGE STUDENTS USING THE TOPSIS METHOD - Marlina, Marlina; Sari, Retno (Jurnal Pilar Nusa Mandiri, 2022)
Internet users in Indonesia aged 16 to 64 years who access the internet on mobile phones as many as 195.3 million. In 2015 the number of online shops was 7.4 million people. Convenience and customer service today are key in improving an online shop. The number of online shop applications available for MSME has difficulty in determining the online shop to determine the right online shop in marketing products among students. The TOPSIS method is used as a method for decision-making because it has a simple and easy-to-understand the concept. This study has five criteria, namely product completeness, interface design, service response, delivery services, and transaction processes. And has 5 alternatives namely shopee, tokopedia, bukalapak, lazada and blibli. In this study obtained from the 5 alternatives, the online shop that is most in demand by students is shopee, this can be seen from the pretension value of 0.89.